Best of most possible worlds: hybrid gene therapy vectors based on parvoviruses and heterologous viruses - Fakhiri, Julia; Grimm, Dirk (Molecular therapy, 2021)
Parvoviruses and especially the adeno-associated virus (AAV) species provide an exciting and versatile platform for the rational design or molecular evolution of human gene-therapy vectors, documented by literature from over half a century, hundreds of clinical trials, and the recent commercialization of multiple AAV gene therapeutics. For the last three decades, the power of these vectors has been further potentiated through various types of hybrid vectors created by intra- or inter-genus juxtaposition of viral DNA and protein cis elements or by synergistic complementation of parvoviral features with those of heterologous, prokaryotic, or eukaryotic viruses. Here, we provide an overview of the history and promise of this rapidly expanding field of hybrid parvoviral gene-therapy vectors, starting with early generations of chimeric particles composed of a recombinant AAV genome encapsidated in shells of synthetic AAVs or of adeno-, herpes-, baculo-, or protoparvoviruses. We then dedicate our attention to two newer, highly promising types of hybrid vectors created via (1) pseudotyping of AAV genomes with bocaviral serotypes and capsid mutants or (2) packaging of AAV DNA into, or tethering of entire vector particles to, bacteriophages. Finally, we conclude with an outlook summarizing critical requirements and improvements toward clinical translation of these original concepts.
Gesehen am 07.01.2022